(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify: - The students ’strategic intelligence level. - The level of academic social adjustment of the female students. - The direction and strength of the relationship between strategic intelligence and academic social adaptation among female students. - The extent of the contribution of strategic intelligence to the academic social adjustment of female students. In the current research, the researcher used the relational descriptive approach, and the research sample consisted of (100) students chosen by the random stratified method, and by (%31) of the female students of the original community, and by (25) students distributed in four stages in Al-Mustansiriya University - College of Basic Education, and it was approved. The researcher in her search on two tools; The first tool is to build a measure of strategic intelligence by reviewing the theoretical framework, literature and studies related to strategic intelligence. As for the second tool, it is the adoption of the academic social adjustment scale, and their psychometric characteristics were verified as (apparent validity - discriminatory validity - construct validity - the relationship of the item score to the total score of the scale - consistency). When processing the current research data statistically using the T-test for two independent samples, the Pearson correlation coefficient, the Cronbach alpha coefficient, the T-test for a one sample, and the simple linear regression analysis; search results yielded: - The students possess a level of strategic intelligence based on the differences between the arithmetic average and the theoretical average. -The students possess a level of academic social adaptation based on the differences between the arithmetic average and the theoretical average. -The existence of a positive correlation between strategic intelligence and academic social adaptation. -The contribution of strategic intelligence by (%24) to the academic social adaptation of kindergarten students. To complement the current research, the researcher presented a number of recommendations and proposals.